Disseminated Gonorrhea Presenting as Liver Abscess in a Patient With Sickle Cell Disease - Kim, Jani M; Pervaiz, Sarah; Sivasubramanian, Geetha (Sexually transmitted diseases, 2022)
Infection caused by Neisseria gonorrhoeae is a global health concern. Occasionally, gonococcal infections may disseminate and cause clinical syndromes, such as arthritis, tenosynovitis, and skin lesions. Here, we report a very rare presentation of a liver abscess due to N. gonorrhoeae in a 29-year-old woman with sickle cell disease without prior genitourinary complaints. The patient was successfully treated using drainage and antimicrobial therapy. Evaluation did not reveal any inherited defects in complement deficiency. It is possible that the underlying immune defects from sickle cell disease and unknown bacterial virulence factors could have contributed to this dissemination. Further research is needed to understand the immunopathogenesis of disseminated gonococcal infections, and efforts to screen and prevent primary infections are ongoing.